Pengaruh Penerapan Model Pembelajaran Giving Question and Getting Answer Terhadap Hasil Belajar Ilmu Pengetahuan Alam Sosial (IPAS) Siswa Kelas IV SD Negeri 29 Ambon - Sengo, Angel Cecilia; Ritiauw, Leonid; Hallatu, Yosepus Anthony (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the giving question and getting answer learning model on IPAS learning outcomes in fourth grade elementary school students. This study uses pre-experimental research that examines the effect of the giving question and getting answer learning model on IPAS learning outcomes in fourth grade students at SD Negeri 29 Ambon. The research design used is a one group pretest and posttest design. The sample used consisted of 19 fourth-grade students at SD Negeri 29 Ambon. The research instruments used were observation, tests, and documentation. Furthermore, the data analysis technique used validation and reliability tests as well as prerequisite analysis tests. The results showed that: 1) The application of the Giving Question and Getting Answer cooperative learning model was very effective in the learning process, 2) By comparing the sig value and the degree of freedom, it can be concluded that Ho is rejected and Ha is accepted because the Sing value of 0.000 < 0.05. This indicates that the application of the Giving Question and Getting Answer learning model has a significant effect on improving student learning outcomes